PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF DILENGKAPI DENGAN HANDOUT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP NEGERI 25 PADANG - Silvina, Novi Rian; Helendra, Helendra; Sari, Liza Yulia (Pendidikan Biologi, 2013)
ABSTRACT            This research is formulated by this the result of a study biology at eight grade student of junior high school 25 Padang that still have under of KKM that is 75. The causes are in the learning process the teacher as a fasilitator, so the student is not creative  and less of interesting in learning process and then there is no hand book that used for students. To avoid  these problems, the reasearcher uses of creative-productive strategy in learning process by handout. The purpose of this research is to know the effect of using  creative-productive learning strategy toward the result of a study biology at eight grade students of junior high school 25 Padang. The design of this research is experimental research. Population of this research is at eight grade students of junior high school 25 Padang. The researcher uses purposive sampling technique. The researcher gets two classes as a sample. They are VIII3 as experimental class and VIII4 as control class. The instrument is used for the research is the result test of study. Based on the analyzing of the data the researcher got the mean of experimental is 80,07 and the mean of control group  is 69,79. The result of the test is taken by using normality test, Homogenites and hypothesis. The result of analyzing the data is used by T-test. The value of t-calculated = 6,08 and t-table = 1,82. Based on the analyzing the data the researcher concluded that the creative-productive learning strategy by handout gave an effective effect toward to the result of a study biology at eight grade students of junior high school 25 Padang.